THE ROLE OF MOTIVATION AND EMOTIONAL ENGAGEMENT IN ENHANCING READING AND WRITING SUCCESS AMONG EFL LEARNERS (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
This study explores the significant role of motivation and emotional engagement in enhancing reading and writing success among English as a Foreign Language (EFL) learners. Drawing on Self-Determination Theory and the Affective Filter Hypothesis, the paper investigates how intrinsic and extrinsic motivation influence learners’ attitudes and performances in literacy tasks. Emotional engagement, including interest, empathy, and personal connection to texts, is also examined as a factor that deepens comprehension and expression. By analyzing recent studies and theoretical frameworks, this article highlights classroom strategies that foster student motivation and emotional involvement, ultimately leading to improved reading comprehension and writing proficiency in EFL contexts.